Legislative basis of the digital ruble platform and main problems in regulation at present - A. M. Musatov (Путеводитель предпринимателя)
In this article we will review the legislative basis of the digital ruble platform, as well as analyze the key aspects of the implementation of the legislative initiative of the digital currency, highlight the potential benefits and challenges associated with this innovation. The emergence of a new instrument in the economy will certainly have a significant impact on domestic and foreign markets, as well as entail changes in the legislation of the Russian Federation. The adaptation of the economy and the legal framework will take place gradually, and participants in digital ruble settlements will need to get used to the new. It is already worth noting that it will take at least two to three years for market participants to get used to the new instrument and for the regulator to make the necessary adjustments to the new instrument. In the next few years it will be necessary to adapt and improve the legislative base for the new instrument. The existing legislative base does not fully allow to carry out operations with the new instrument, in the next few years, it will be necessary to make the necessary changes to the current legislation of the Russian Federation, as well as to adopt new draft laws. In this paper we will consider the business sector, which in the first stages will be the first participants who will be able to assess the full possible potential of the new financial instrument and propose new draft laws to improve the regulation of the digital ruble. It is worth noting that the business sector is already actively proposing new bills to improve the digital ruble platform, as well as pointing out gaps in the legislative framework related to the regulation of the digital ruble. Thus, the business sector will play a crucial role in finalizing the legislative platform to regulate the digital ruble in the Russian Federation.